STRATEGI UNTUK MENINGKATKAN KINERJA PADA RUMAH SAKIT KELUARGA “ABC” - Ana Rusmardiana (JABE (Journal of Applied Business and Economic), 2015)
“ABC Family Hospital” has been around long enough to operate in Jakarta as the hospital family, i.e., approximately 26 years up to the year 2015. Various improvements and as well as the development effort has been carried out, including the number of employees. However, such an assessment would have increased the efficiency and effectiveness of resource use is still considered less, similarly to the predictable quality still considered still not satisfy with what was expected by the management. To this end, looked at the need to restructure and improve the strategy that has been done in order to achieve what is the vision, mission and objectives are clear and exact against the company that manages the hospital. The very important thing is done mainly by the presence of competittor-competittor which is getting tight like other private hospitals, clinics, clinics and doctors ' practices, and also to maintain accredited Hospitals in question.